Effect of chemical structure of lignite and high-volatile bituminous coal on the generation of biogenic coalbed methane. (1st June 2019) - Shao, Pei; Wang, Aikuan; Wang, Wenfeng
Abstract: Biogenic coalbed methane has been attracted much attention due to massive reserves and green performance, but the current research is relatively weak. To further investigate its formation mechanism, the experimental simulation of biogas generation was performed by using lignite, high-volatile bituminous coals and their treated coals as substrates for 90 days. The results show that the lignite has a greater biogas potential than high-volatile bituminous coal in this study. Total gas production in lignite groups (L-BZ-1 and L-LJ-1) is 12.6% more than the bituminous coal groups in the experimental simulation. This is because the lignite has a low degree of thermal evolution and rich in soluble organic matter: chloroform asphalt "A" (CAA), which plays an important role in microbial metabolism to produce biogas. The CAA in coal has a conversion rate of 3.08 mL/g into biogas in this experimental simulation. The saturated hydrocarbons and nonhydrocarbons are more biodegradable components in the CAA. In saturated hydrocarbons, the n -alkanes with shorter chains or an odd carbon number are preferentially degraded. In the experimental simulation, biogas generation results in the consumption of a large number of organic matters with heteroatomic groups such as hydroxyl, carboxyl, pyridine and nitrogen oxides. Aliphatics show a stronger bioactivity than aromatics. The aromatic structure in coal is a few biodegraded in the later stage.